Co-creating conditions for belonging in higher education: an appreciative inquiry research study - Bauer, Tamara (Kansas State University, 2024)
This qualitative research study explored how undergraduate students at a public four-year land grant university can co-create a sense of belonging through an appreciative inquiry (AI) process. The study employed a strengths-based and generative approach to investigate the experiences of students within the same student organization, focusing on how these experiences contribute to a deeper understanding and practice of belonging. Utilizing AI as the research methodology, this study followed the 5-D AI cycle—define, discover, dream, design, and deliver—to facilitate a structured exploration of belonging among students, and to gather data on students' experiences and perceptions of belonging. Participants engaged in focus group discussions and activities that helped them reflect on their experiences and envision future possibilities for co-creating belonging on campus. The research findings highlight several key themes that contribute towards the co-creation of a sense of belonging among students, including (a) safety, acceptance, and inclusion, (b) organizational structure and dynamics, (c) meaningful interpersonal connections, and (d) purpose and investment. The AI process not only facilitated a deeper understanding of these themes but also empowered participants to co-create strategies for enhancing belonging among themselves. By focusing on positive experiences and collective aspirations, the study demonstrates how AI can be a powerful tool for fostering inclusive and supportive environments in higher education and can be utilized as both a philosophy and method in qualitative research.
Keywords: Belonging; College students' sense of belonging; Appreciative inquiry; Co-create; Higher education